ISOMER--Augmenting Software Testing Confidence by Automated Comparison with a Lightweight Model. - Kulp, Darren (My University, 2009)
Non-algorithmic constraints on software development can hinder testing efforts by creating pitfalls for the programmer or by hiding data-dependent errors in complex codes. The ISOMER framework improves testing efficacy and confidence by further automating software component and program testing. Using a familiar expression syntax to deffine constraints on the random stimulus generated, ISOMER subjects software interfaces to dynamically-generated test cases, adding value over time.
Color poster with text and chart describing research conducted by Darren Kulp, advised by Daniel J. Ernst.
Keywords: ISOMER (Software); Computer software--Development; Computer software--Testing; Posters